DEFINITIONS OF THE REAL ESTATE TURNOVER SYSTEM - V. A. Petrushkin (Russian Journal of Economics and Law)
Objective: to study the principles and the role of legislative definitions within the various research methods for modeling functions of legal models of the civil rights objects. Methods: method of comparative analysis and abstract method. Results: the analysis of scientific approaches defines simulation as a method of research, which remains weak in legal sciences, its relevance and topicality are ignored. The author proposes systematization of real contracts as to their content - the type of property rights, the transfer of which is the subject of agreement. The work expands the concept of "property law" in statics, as a result of comparison of the "legal model" concept with other similar terms. The conclusion is made about the existence of separate legal category in modern science. Scientific novelty: the modeling principles in the theory of law are not fully established, in connection with which the author gives the definition of the legal modeling factors in the sphere of the turnover of the civil rights objects and their classification. Practical value: the identified approaches provide for the possibility to study the principles of development of the approaches functioning mechanism, as well as to map the ideal model with really existing social relations in the sphere of real estate turnover.